A right of Christian faithful to the just process - LESZCZYŃSKI, GRZEGORZ (Prawo Kanoniczne, 2013)
In accord with the can. 1397 of Code of Canon Law euthanasia, correctly understood, is unquestionably repudiated by the Catholic moral tradition and is regarded by the canonical scholarly tradition as a species of homicide. Canon 1397 subjects those committing "homicide" to "a just penalty. In this article the author is trying to explane the main norms in this topic and to present the moral aspects of euthanasia as a sin against the human life.